La contribution de la prosodie et de la théâtralisation des récits à l’âge préscolaire : un levier pour la représentation des émotions ? - Sanchez, Lisa; Creissen, Sara; Blanc, Nathalie (Canadian Journal of Education/Revue canadienne de l'éducation, 2026)
In order to improve the performance of French-speaking students in listening comprehension of stories, this study aimed to explore the optimal conditions for stimulating these skills from preschool age. We compared three ways of presenting children’s literature in order to assess their effects on emotional comprehension. In the first, the story was told with weak prosody, in the second, the prosody was marked, and in the third, the story was dramatized. The ability of children aged three to five years to understand the emotions of the characters in the stories was investigated in two complementary studies in order to determine the most favourable presentation modality. The results of these studies indicate that the children scored better in a dramatized reading situation and when a marked prosody was used, with a notable advantage for the dramatized reading situation, which would favour the tracking of certain emotions that are still underdeveloped at preschool age. This research highlights the value of using story dramatization to promote young children’s emotional understanding of stories.